2014
DOI: 10.1038/srep05793
|View full text |Cite
|
Sign up to set email alerts
|

Low blood cell counts in wild Japanese monkeys after the Fukushima Daiichi nuclear disaster

Abstract: In April 2012 we carried out a 1-year hematological study on a population of wild Japanese monkeys inhabiting the forest area of Fukushima City. This area is located 70 km from the Fukushima Daiichi Nuclear Power Plant (NPP), which released a large amount of radioactive material into the environment following the Great East Japan Earthquake of 2011. For comparison, we examined monkeys inhabiting the Shimokita Peninsula in Aomori Prefecture, located approximately 400 km from the NPP. Total muscle cesium concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 15 publications
1
54
0
Order By: Relevance
“…; Ochiai et al . ), the barn swallow (a decrease in number) (Bonisoli‐Alquati et al . ) and the goshawk (a reproductive difficulty) (Murase et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Ochiai et al . ), the barn swallow (a decrease in number) (Bonisoli‐Alquati et al . ) and the goshawk (a reproductive difficulty) (Murase et al .…”
Section: Introductionmentioning
confidence: 99%
“…Information on the biological effects of this accident has been accumulating gradually; the accident has likely affected various animals and plants such as birds and insects (Møller et al , ; Mousseau and Møller ), aphids (Akimoto ), rice plants (Hayashi et al ), Japanese monkeys (Ochiai et al ), barn swallows (Bonisoli‐Alquati et al ), goshawks (Murase et al ), wild mice (Kubota et al ), fir trees (Watanabe et al ), and the pale grass blue butterflies. In contrast, there are reports that detected no effects in bull and mouse testes (Yamashiro et al ; Okano et al ).…”
Section: Introductionmentioning
confidence: 99%
“…A study on earthworms also demonstrated that animals from sites where radiation level was as low as 2.8 μSv/h had higher DNA damage than animals from control sites22. A recent study of wild Japanese macaques ( Macaca fuscata ) found that individuals from Fukushima had lower white blood cell (WBCs) and red blood cell counts (RBCs), lower hemoglobin concentration and lower hematocrit values than those sampled in the Shimokita peninsula, at a distance of 400 km from the FDNPP23. Vitamin A levels of streaked shearwaters ( Calonectris leucomelas ) sampled in colonies exposed to contamination from the FDNPP were lower than in animals from a colony that was not reached by the plume24.…”
mentioning
confidence: 99%
“…With a few notable exceptions162324, all studies conducted so far have at most analyzed the concentrations of radioisotopes in the tissues of organisms, but neglected the assessment of markers of their potential biological effects. The results that we describe represent the first extensive investigation of the potential genotoxicity of measured radiation exposure in any wild population of birds from the Fukushima region.…”
mentioning
confidence: 99%